Digitalization and economic growth: A comparative analysis of Sub-Saharan Africa and OECD economies. (March 2020) - Myovella, Godwin; Karacuka, Mehmet; Haucap, Justus
Abstract: This paper examines the contribution of digitalization to economic growth of Sub Saharan Africa (SSA) in comparison with the Organization for Economic Cooperation and Development (OECD) economies. The main reason for comparing the most and the least developed countries to measure the effects of digitalization is to have an insight of whether such effects depend on the levels of development of the country. New technologies in Sub Saharan Africa are assumed to have played significant roles in economic activity, including accessibility of communications, which was impeded by poor infrastructure, accommodation of the poor majority who were initially financially excluded from mobile banking and participation of small and medium enterprises (SMEs) in e-commerce. On the other hand, due to the effects of digitalization, least developed countries in SSA have been facing a premature deindustrialization. This study employs a panel dataset consisting of 11 years from 2006 to 2016 for 41 SSA and 33 OECD economies and we use the generalized linear methods of moments (GMM) estimators. The results show that digitalization has a positive contribution to economic growth in both groups of countries. The effect of broadband internet is minimal for SSA compared to OECD countries, whereas the impact of mobile telecommunications is higher in SSA compared to the OECD counterpart. These results are particularly interesting as less advanced technologies create more opportunities in the least developed countries since there is more space for improvement. With respect to policy implications, this study recommends that SSA governments should invest more in ICT along with other infrastructures, so as to benefit from digitalization and to realize significant economic growth. Highlights: Examines the contribution of digitalization to economic growth of Sub Saharan Africa (SSA) in comparison with the OECD economies. Analyses the positive and negative effects of digitalization developing countries. Employse a panel data set for 74 countries and uses GMM estimators. Finds that digitalization has a positive contribution to economic growth in both groups of countries. Finds that broadband internet and mobile telecommunications have different impacts for OECD and SSA countries.